Relevance of Statistics Education in Sustainable Development. (2017)
This study is designed to examine the relevance of Statistics in sustainable development. Current thinking about statistics should be in all human development and practices which reveals that the application of statistics and statistical methods in the construction of scientific knowledge in business, economics, accounting, banking, management & administration, astronomy, natural sciences, research, politics & election process, housing system, health sciences and weather forecasts as well as, to propose some improvement actions cannot be rule out, it is highly important. Statistics should no longer be seen as a side attraction but to be tolerated and allowed in all sectors. The challenges confronting the nation could be discussed and statistics has provided solutions and an eye opener for all. Finally, it was observed that for a nation to develop and be sustainable statistics should be implemented.